The ETS Inhibitor YK-4-279 Suppresses Thyroid Cancer Progression Independent of TERT Promoter Mutations - Xue, Junyu; Li, Shiyong; Shi, Peijie; Chen, Mengke; Yu, Shuang; Hong, Shubin; Li, Yanbing; Liu, Rengyun; Xiao, Haipeng (Frontiers in Oncology, 2021)
Hotspot mutations in the core promoter region of the telomerase reverse transcriptase (TERT) gene have been well established to associate with aggressive clinical characteristics, radioiodine refractory, tumor recurrence and mortality in thyroid cancer. Several E-twenty-six (ETS) transcription factors were reported to selectively bound to the mutant TERT promoter and activated TERT expression. In this study we aimed to investigate whether TERT promoter mutations confer sensitivity to ETS inhibitor YK-4-279 in thyroid cancer cells and whether this inhibitor could be served as a potential therapeutic agent for thyroid cancer. In vitro assays showed that YK-4-279 treatment sharply suppressed cell viability, colony formation, migration and invasion, as well as induced cell cycle arrest and apoptosis in a panel of thyroid cancer cells. The cell viability after YK-4-279 treatment were similar between cell lines harboring mutant and wild-type TERT promoter. Furthermore, YK-4-279 treatment reduced both luciferase activity and mRNA expression of TERT independent of TERT promoter mutation status. Data from RNA-seq further revealed that YK-4-279 significantly affected biological processes including DNA replication and cell cycle. Reduced DNA helicase activity and decreased expression of several helicase genes were observed. Moreover, YK-4-279 significantly inhibited tumor growth and induced apoptosis in a xenograft mice model. Thus, ETS inhibitor YK-4-279 suppressed TERT expression and conferred anti-tumor activity in a TERT promoter mutation-independent manner, and it could be a potential agent for the treatment of advanced thyroid cancers.